Queen of Katwe [videorecording (DVD)] - Oyelowo, David; Nyong'o, Lupita; Nalwanga, Madina; Crothers, Tim (Disney, 2017)
Based on the vibrant true story of a young girl from the streets of rural Uganda whose world rapidly changes when she is introduced to the game of chess, and, as a result of the support she receives from her family and community, is instilled with the confidence and determination she needs to pursue her dream of becoming an international chess champion.